PENGARUH PEMBERIAN MEDIA PUZZLE DAN MODEL PEMBELAJARAN TALKING STICK TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X MAN KOTO BARU DHARMASRAYA - Ningsih, Sri; Sudirman, Sudirman; Widiana, Rina (STKIP PGRI Sumbar, 2013)
ABSTRACT The background of this research by the low learning outcome biology of students MAN Koto Baru Dharmasraya, which is caused by several factors such as learning less interesting and boring, teachers tend to use lecture method and discussion, learning does not come with media and students are less activity and creative in learning. One attempt to do is by giving media puzzle and talking stick learning model. This research aimed to determine the effect media puzzle and talking stick learning model on learning outcome biology for students class X MAN Koto Baru Dharmasraya academic year 2012/2013. This type of research is experimental research, which is carried on class X semester 2 of academic year 2012/2013 in MAN Koto Baru Dharmasraya in May 2013, with the research design Randomized Control Group Only Design. The population in this research is the students of class X MAN Koto Baru Dharmasraya academic year 2012/2013 which consists of three class. The method of sample is by using Purposive Sampling, to determine the class of samples was done by the draw in order to obtain a sample class, class X1 as the experimental class and the control class as a class X2. The instrument used is the final test of learning outcome in the form of objective test of 30 items. Data analysis was performed with analysis of test-t. Be based on analysis obtained an average grade experimental learning result is 72,56 with a standard deviation of 7,82, while the control class is 66,42 with a standard of 10,73. Of the test-t analysis tobtained (2,05) >ttable (1,68) so it can concluded that the subjects with media puzzle and talking stick learning model can improve learning outcome biology class X MAN Koto Baru Dharmasraya